Tourism Communication Strategies for Promoting Cultural Heritage in Sumenep: Analyzing Stakeholder Roles and Engagement - Sufa, Siska Armawati; Riyadi, Slamet; Djoko Baruno, Agustiawan; Priyambodo, Priyambodo; Brumadyadisty, Garry (Badan Riset dan Inovasi Daerah Provinsi Jawa Timur, 2024)
This research investigates the tourism communication strategies used to promote Sumenep’s cultural heritage, focusing on the roles and engagement of key stakeholders such as local government, tourism operators, community leaders, and cultural institutions. The study, using a qualitative approach and thematic analysis via NVIVO software, examines how communication is structured and coordinated among these groups to enhance tourism. The findings highlight that successful tourism communication relies on strong collaboration between local authorities and community leaders, with cultural events and heritage preservation playing a central role. The research concludes by recommending improved communication strategies through stakeholder alignment and the inclusion of local cultural narratives for better tourism development in the region.